PENGARUH MEDIA PEMBELAJARAN ICT BERBASIS CLASSROOM DAN QUIZIZ TERHADAP MINAT BELAJAR SISWA PADA MATERI STATISTIKA - Deni Andika Nur Pratama; Loviga Denny Pratama (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2024)
This research aims to examine the influence of classroom-based ICT learning media on students' interest in learning in statistics material for class VIII B at MTs SA Tarbiyatus Shibyan Guyangan Krucil Probolinggo. The approach applied in this research is a case study using quantitative methods. Data collection was carried out through observation, interviews, questionnaires, tests, and documentation. The researchers' findings identified that the results of the research that had been carried out showed that in terms of the influence of classroom and quiziz-based ICT learning media on students' interest in learning mathematics taken by research subjects with a total of 20 students in one class VIII B at MTs SA Tarbiyatus Shibyan with results obtained sig < α (0.001 < 0.05) then H0 is rejected, the regression line equation is accepted or the variable is the influence of classroom-based ICT learning media (X1) and quizzes (X2) on interest in learning (Y). And getting Fhit = 10.929 > Ftab = 3.592 then H0 is rejected, the regression line equation is accepted or the variables X1 (Classroom Based ICT Learning Media) and And for the residual data normality test, it is found that sig > α (0.116 > 0.05) then H0 is rejected, there is a difference between the residual data and normal data, D_count= 0.215 <〖 D〗_tabel= 0.29407 (5%) then H0 is accepted , there is no difference between residual data and normal data. So in this research developing ICT-based learning media based on Classroom and Quiz really influences students' interest in learning mathematics.